Makna Penamaan Desa Kecamatan Pangkalan Kuras Kabupaten Pelalawan - May Helda; Angel Cristina; Fadillah Fitri; Rini Angraini (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to describe the names of village in Pangkalan Kuras district, Pelalawan district Pangkalan Kuras. This research includes qualitative research using ethnographic methods. The data collection technique used is observasion, interview, note taking anda listening techniques. Data analysis tecchniques used in this research are data reduction, data presentation, and concludion drawing/data verification. Based on the research results, the naming of names in the village of Pangkalan Kuras sub-district consists of aspects of embodiment, aspect of culture and aspect of society.